Petroleum Industry Act and Investment in Nigeria - Kunemoemi, Zacchaeus (NIU Journal of Social Sciences, 2026)
This paper investigates the impact of petroleum industry act on investment in Nigeria over the period 1990–2025. Petroleum Industry Act Dummy, Crude Oil Price, Oil Revenue and Oil Production was used as a stand in for petroleum industry act while Gross Fixed Capital Formation was used as a proxy for Investment. Secondary data were sourced from the Central Bank of Nigeria (CBN), statistical Bulletin, World Bank World Development Indicator (WDI) and OPEC, Annual Statistical Bulletin. The Augmented Dickey-Fuller unit root test was employed to examine the stationarity properties of the variables, while the Auto-Regressive Distributed Lag model was utilized to estimate both short-run and long-run dynamics. The bounds testing approach confirms the existence of a long-run relationship between the variables. Empirical findings reveal petroleum industry act dummy and oil production had a positive but significant relationship with gross fixed capital formation while oil price and oil revenue had a negative and insignificant relationship with gross fixed capital formation. It was concluded that petroleum industry act had a significant impact on investment in Nigeria. It was recommended amongst other that the Nigerian Upstream Petroleum Regulatory Commission and the Nigerian National Petroleum Company Limited should ensure strict and transparent implementation of the Petroleum Industry Act by strengthening regulatory certainty, simplifying licensing procedures, and enforcing compliance. This will sustain investor confidence and further stimulate capital formation in the petroleum sector. Keywords: Petroleum Industry Act Dummy, Crude Oil Price, Oil Revenue, Oil Production Gross Fixed Capital Formation was used as a proxy for Investment.